Pemberdayaan Masyarakat Pertambangan Melalui Kewirausahaan - Endang Abubakar; Aprisa Rian Histiarini; Hilmi Hilmansyah; Ummi Hanifah Marshush (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Community empowerment is an effort made by the community, with or without external support, to improve their lives based on their own resources through efforts to optimize their resources and increase their bargaining position. The aim of this community service activity is to guide and assist mining area communities in entrepreneurship. This community activity was carried out on November 25–30, 2023, in the mining area of PT Hillconjaya Shakti, which is located in Lameruru Village, Langgikima District, North Konawe Regency, Southeast Sulawesi Province. This community service activity was carried out with several activities, namely: (1) delivery of material about entrepreneurship by lecturers at Muhammadiyah University of Sorong for 1 day; (2) assistance in entrepreneurship for 2 days; and (3) community empowerment in entrepreneurship for 2 days. One of the efforts undertaken is to produce raw food ingredients into ready-to-eat food. Apart from the fast food business, the community also participates in the grocery store business. What is meant by grocery store here is a service that offers various daily necessities products with a small minimarket concept.